The Process of building career paths in health services in the Americas : situation analysis and prospects for technical cooperation - Castellanos, Jorge (PAHO Washington, DCUS, 2007)
Analyses firstly the characteristics, technical aspects, functions and dynamic of the process of building the career path in health services, the critical factors for achieving the proposed aims and the scope of the process as a possible line of action to resolve some of the problems facing health workers; and secondly, to present the latest developments in the Americas.